Pseudorabies virus tegument protein US2 antagonizes antiviral innate immunity by targeting cGAS-STING signaling pathway - Kong, Zhengjie; Chen, Xing; Gong, Lele; Wang, Lele; Zhang, Yifeng; Guan, Kaifeng; Yao, Wanzi; Kang, Yu; Lu, Xinyi; Zhang, Yuhang; Du, Yongkun; Sun, Aijun; et al. (Frontiers in Immunology, 2024)
The cGAS-STING axis-mediated type I interferon pathway is a crucial strategy for host defense against DNA virus infection. Numerous evasion strategies developed by the pseudorabies virus (PRV) counteract host antiviral immunity. To what extent PRV-encoded proteins evade the cGAS-STING signaling pathway is unknown. Using 2 US2 stably expressing cell lines and US2-deficient PRV model, we revealed that the PRV tegument protein US2 reduces STING protein stability and downregulates STING-mediated antiviral signaling. To promote K48-linked ubiquitination and STING degradation, US2 interacts with the LBD structural domain of STING and recruits the E3 ligase TRIM21. TRIM21 deficiency consistently strengthens the host antiviral immune response brought on by PRV infection. Additionally, US2-deficient PRV is less harmful in mice. Our study implies that PRV US2 inhibits IFN signaling by a new mechanism that selectively targets STING while successfully evading the host antiviral response. As a result, the present study reveals a novel strategy by which PRV evades host defense and offers explanations for why the Bartha-K61 classical vaccine strain failed to offer effective defense against PRV variant strains in China, indicating that US2 may be a key target for developing gene-deficient PRV vaccines.